Review of the development of the hydrogen maser technique and a brief introduction to its space applications - Dai, Jiayu; Liu, Tiexin; Cai, Yong; Chen, Zhichun; Li, Qi (Frontiers in Physics, 2022)
Since 1960, when the first hydrogen frequency standard, also called Microwave Amplification by Stimulated Emission of Radiation (MASER), was made in Ramsey’s laboratory at Harvard University, the valuable frequency stability performance, and the technique development, of H MASER has been closely related to the scientific research. Especially, a variety design of H MASER has been made for the demands of space science applications, such as the Deep Space Network (DSN), and the Gravity Probe (GP) experiment. H MASER is one of the three well-developed microwave atomic frequency standards, and widely used over world, ground based and on-board based. Along with the upgrades of the frequency stability performance of H MASER, contributions to the improvements of the knowledge of the world have been made.